Comparison of the efficacy of combined epidural anesthesia with general anaesthesia alone to attenuate hemodynamic responses and perioperative analgesia in laparoscopic cholecystectomy patients - Bandewar, Aishwarya; Naik, Shweta; Kokne, Manish; kaur, Sugampreet (International Journal of Research in Medical Sciences, 2019)
Background: The aim of the study was to compare the efficacy of combined GA-Epidural Anesthesia (CEGA) with GA alone to attenuate hemodynamic responses and perioperative analgesia. Method: Authors conducted a prospective, randomized, double blind study, in which 60 patients undergoing laparoscopic cholecystectomy. Group A received (n=30) received GA and Group B (n=30) received combined GA and Epidural Anaesthesia (CEGA). Authors analyzed the effect of combined epidural general anaesthesia as compared to plain general anaesthesia with regard to hemodynamic parameters (heart rate, systolic and diastolic blood pressure), intraoperative anaesthetic requirement (intraoperative requirement of propofol), recovery score and postoperative analgesia (VAS score). Results: Authors found significant decrease in the heart rate, systolic and diastolic blood pressure in response to stress response to pneumoperitoneum in combined epidural general anaesthesia (CEGA) group compared to plain general anaesthesia (GA) group. Total amount of propofol required intraoperatively was less in CEGA group than in GA group. Recovery score and pain score (VAS) score were also compared which were better in CEGA group than in GA group. There were no significant intraoperative and postoperative complications noted in both the groups. Conclusion: Authors concluded that the use of epidural along with general anaesthesia helps in attenuating hemodynamic changes due to stress response to pneumoperitoneum, which results in maintaining stable intraoperative and postoperative hemodynamics during laparoscopic cholecystectomy surgery. Combining epidural to general anaesthesia results in rapid recovery as compared to plain general anaesthesia and also helps in providing good postoperative analgesia.